Large-volume, high-fluidity, crack-resistant concrete for ultra-high altitude areas and preparation method thereof

By using medium-thermal silicate cement and other combination agents in concrete at ultra-high altitude areas, the flowability and stability of concrete in low-pressure environments are solved, crack resistance and frost resistance are improved, and concrete is ensured. Long-term service life and visual quality.

CN118290096BActive Publication Date: 2024-12-20CHINA CONSTR SECOND ENG BUREAU LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410397548.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-03
Publication Date
2024-12-20
Estimated Expiration
2044-04-03

AI Technical Summary

Technical Problem

Concrete in ultra-high altitude areas exhibits low viscosity, unstable bubbles, rapid slump loss, high risk of early cracking, poor anti-freeze and cracking performance under low air pressure and low humidity environments, and it is difficult to ensure strength. Improve crack resistance, frost resistance and chemical corrosion resistance.

Method used

Using a combination of medium-heat silicate cement, foam stabilizing and humidifying agent, anti-crack toughening agent, fly ash, ore powder, fine aggregate, retarding and efficient water reduction agent and gas induction agent, through adjustment of ratio and process Process, delay initial settling time, improve the flowability and stability of concrete, reduce hydration heat and shrinkage, and enhance crack and frost resistance.

Benefits of technology

The good flowability and filling capacity of concrete are achieved in ultra-high altitude areas, reducing the risk of early cracking, improving the strength, frost resistance, chemical corrosion resistance and homogeneity of concrete, ensuring the long-term service life and appearance of concrete quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004774494700000061
    Figure BDA0004774494700000061
  • Figure BDA0004774494700000071
    Figure BDA0004774494700000071
  • Figure BDA0004774494700000081
    Figure BDA0004774494700000081
Patent Text Reader

Abstract

The invention discloses a large-volume, high-fluidity, crack-resistant concrete for ultra-high altitude areas and a preparation method thereof, which comprises, by weight, 8% to 16% cement, 0.0001% to 0.001% of a foam stabilizer and humidity regulator, 0.1% to 1.0% of an anti-cracking toughening agent, 3% to 6% of fly ash, 0% to 4% of mineral powder, 28% to 35% of fine aggregate, 42% to 45% of coarse aggregate, 0.001% to 0.002% of a slow-setting high-efficiency water-reducing agent, 0.001% to 0.002% of an air-entraining agent, and 5.5% to 6.5% of water. The large-volume, high-fluidity, crack-resistant concrete for ultra-high altitude areas provided by the invention has good stability and fluidity, does not produce segregation, and has a small loss of 4h slump over time; the risk of early cracking of the concrete is low, and the strength and durability of the concrete are excellent. The concrete can be applied to concrete buildings and structures in ultra-high altitude areas, and has broad application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building materials, and specifically relates to a large-volume, high-fluidity, crack-resistant concrete for ultra-high altitude areas and a preparation method thereof. Background Art

[0002] Due to the special geographical location of ultra-high altitude areas, the ambient temperature is low, the air pressure is low, the humidity is low, the temperature difference between day and night is large, the ultraviolet rays are strong, and the wind speed is high, which makes the concrete performance in ultra-high altitude areas very different from that in normal pressure areas. In my country's normal pressure areas, low water-cement ratio, large amount of mineral admixtures, ordinary Portland cement, high-efficiency water reducer and appropriate sand ratio are generally used to prepare large-volume concrete. In ultra-high altitude areas, during the construction of such large-volume concrete, the viscosity of the cement paste is low, and the generated bubbles are easier to escape from the concrete mixture. Compared with normal pressure areas, the bubbles introduced into the concrete last for a shorter time, the bubbles are larger and easier to break. Due to the poor stability of the bubbles, the air content and workability of the concrete are greatly reduced, resulting in a rapid loss of concrete slump over time. In order to improve the fluidity of the concrete mixture, the amount of water reducer will be larger than that of the concrete in normal pressure areas, which will reduce the viscosity of the cementitious material and the air content of the concrete, making the bleeding and segregation of the concrete more serious. At the same time, in ultra-high altitude areas, low pressure, low humidity and strong ultraviolet radiation are obvious. During the preparation and construction of concrete, the water loss rate inside it is faster than that in the normal pressure area, and the degree of cement hydration is also constantly decreasing. At the same time, the shrinkage of concrete is aggravated, and the overall strength, impermeability and chemical corrosion resistance of concrete are reduced. The above conditions lead to poor homogeneity of concrete, high brittleness of concrete, and the surface structure of concrete is susceptible to severe freeze-thaw damage, poor crack resistance, significantly reduced anti-freeze and crack resistance, poor appearance quality of components, and large surface cracks. Compared with large-volume concrete in normal pressure areas, the risk of early cracking is much greater, and the durability of concrete such as anti-freeze, anti-permeability, and chemical corrosion resistance is basically lost. This requires that large-volume crack-resistant concrete in ultra-high altitude areas must not only reduce the hydration heat, but also have higher crack resistance and anti-freeze ability, as well as higher chemical corrosion resistance and sensory quality on the basis of ensuring strength. At the same time, it is also necessary to ensure that the comprehensive indicators such as the fluidity and anti-segregation of concrete mixtures, the durability of concrete and construction performance are balanced and coordinated. Summary of the invention

[0003] Based on the above deficiencies in the prior art, the present invention provides a large-volume, high-fluidity, crack-resistant concrete for ultra-high altitude areas, so as to improve the poor stability of concrete mixtures in ultra-high altitude areas, large slump loss over time, large concrete hydration heat, high cracking risk, poor apparent quality, and poor durability of concrete such as frost resistance and chemical corrosion resistance compared with large-volume, high-fluidity, crack-resistant concrete in normal pressure areas. At the same time, it solves the contradiction between the early crack resistance of concrete in ultra-high altitude areas and the strength, durability, and workability indicators, and the contradiction between the fluidity of concrete and cohesion and water retention, thereby ensuring the normal service life and sensory quality of concrete main projects in ultra-high altitude areas for one hundred years.

[0004] The technical solution adopted by the present invention to solve the above technical problems is as follows:

[0005] The invention discloses a large-volume and high-fluidity anti-cracking concrete for ultra-high altitude areas, comprising cement, a foam stabilizer and humidity regulator, an anti-cracking toughening agent, fly ash, mineral powder, fine aggregate, coarse aggregate, a slow-setting high-efficiency water reducing agent, an air entraining agent and water. The concrete comprises 8% to 16% of cement, 0.0001% to 0.001% of foam stabilizer and humidity regulator, 0.1% to 1.0% of anti-cracking toughening agent, 3% to 6% of fly ash, 0% to 4% of mineral powder, 28% to 35% of fine aggregate, 42% to 45% of coarse aggregate, 0.001% to 0.002% of slow-setting high-efficiency water reducing agent, 0.001% to 0.002% of air entraining agent and 5.5% to 6.5% of water in a weight ratio.

[0006] Preferably, the cement is medium-heat silicate cement, with a strength grade of not less than 42.5 and a specific surface area of ​​300 to 350 m 2 / kg.

[0007] Preferably, the foam stabilizing and humidity regulating agent is a combination of any two or more of polyvinyl alcohol, calcium stearate, methyl cellulose, carboxymethyl cellulose, carboxymethyl hydroxyethyl cellulose, hydroxypropyl cellulose or polyacrylate, and the viscosity of the foam stabilizing and humidity regulating agent is 20×10 5 ~200×10 5 Pa·S, water absorption rate is 10% to 20%.

[0008] Preferably, the anti-cracking toughening agent is a composition of silica powder and metakaolin, the content of SiO2 in the anti-cracking toughening agent is not less than 90%, the content of Al2O3 is not less than 5%, and the particle size of the anti-cracking toughening agent is 50 to 200 nm.

[0009] Preferably, the fly ash is Class F II fly ash, and its water requirement ratio is 90% to 100%; the slag powder is granulated blast furnace slag powder of grade S75 or above, and its activity index is not less than 75%, and its specific surface area is not more than 450m 2 / kg, loss on ignition is not more than 2.5%.

[0010] Preferably, the fine aggregate is one of machine-made sand, river sand or mixed sand, and its fineness modulus is 2.5-2.9; when the sand is machine-made sand, the stone powder content in the machine-made sand is 5%-10%; when the sand is river sand, the mud content of the river sand is not more than 2.0%; when the sand is mixed sand, the mud block content in the mixed sand is not more than 1.0%; the coarse aggregate is continuously graded crushed stone with a particle size of 5-30 mm, and the type of crushed stone is one of limestone, basalt, andesite, gneiss or quartzite, among which 5-10 mm graded crushed stone, 10-20 mm graded crushed stone and 20-30 mm graded crushed stone need to be mixed in proportion, and the compact porosity of the mixed crushed stone is not more than 40%.

[0011] Preferably, the retarding high-efficiency water reducer is a combination of any two or more of polycarboxylates, aminosulfonates, naphthalenesulfonic acid formaldehyde condensates, hydroxycarboxylates or phosphates, and the water reduction rate of the retarding high-efficiency water reducer is not less than 30%, the initial setting time is not less than 110 minutes, and the setting time difference is 100 minutes to 120 minutes.

[0012] Preferably, the air entraining agent is a combination of any two or more of rosin soaps, triptolide saponins or polyether polyols, and the water reduction rate of the air entraining agent is not less than 8%, and the air content is not less than 4%.

[0013] Another technical problem to be solved by the present invention is to provide a method for preparing the above-mentioned large-volume, high-fluidity, crack-resistant concrete for ultra-high altitude areas, comprising the following steps:

[0014] S01. Use a forced mixer to add cement, fly ash, mineral powder and anti-cracking toughening agent in proportion and stir for 30 seconds, wherein the stirring speed of the forced mixer is 60-100r / min;

[0015] S02, continue to add water to the forced mixer and stir for 30 seconds, then add air entraining agent, slow setting high-efficiency water reducing agent and foam stabilizing and humidity regulating agent and continue stirring for 30 seconds;

[0016] S03, continue to add sand and gravel into the forced mixer and mix for 30 seconds;

[0017] S04. Discharge the evenly mixed concrete from the mixer.

[0018] Compared with the prior art, the present invention is beneficial in that:

[0019] 1. The large-volume, high-fluidity, crack-resistant concrete for ultra-high altitude areas of the present invention uses medium-heat silicate cement as a base material, and cooperates with various components to delay the initial setting time of concrete, so that the large-volume, high-fluidity, crack-resistant concrete mixture has good fluidity and strong filling capacity in an ultra-high altitude low-pressure environment, and the 4h slump loss over time is small, which can easily meet the construction requirements. At the same time, the early temperature rise of concrete is reduced, the temperature stress and shrinkage of concrete are reduced, and the risk of early cracking is reduced.

[0020] 2. The large-volume, high-fluidity, crack-resistant concrete for ultra-high altitude areas of the present invention has good stability in ultra-high altitude and low-pressure environments by adding a foam-stabilizing and humidity-regulating agent and an anti-cracking toughening agent, and by reasonably grading coarse and fine aggregates. This improves the homogeneity of the concrete, and at the same time, the cementitious material can be replenished with water during the hydration process. The density of the concrete is enhanced, which slows down the evaporation of water in the concrete and reduces early shrinkage. This not only reduces the risk of early cracking of the concrete, but also greatly improves the strength, frost resistance, chemical corrosion resistance and impermeability of the concrete.

[0021] 3. The large-volume, high-fluidity, crack-resistant concrete prepared by the process of the present invention can reduce the dosage of the retarding water-reducing agent while achieving the construction fluidity, improve the slurry viscosity, reduce the loss of air content of the concrete mixture, and reduce the internal and external defects of the hardened concrete, thereby effectively improving the homogeneity of the concrete, reducing the shrinkage of the concrete, and reducing the risk of concrete cracking. The concrete has a 3-day strength tensile-compression ratio greater than 8%, a 56-day compressive strength of 40-75Mpa, a frost resistance grade greater than F450, a permeability grade not less than P14, an electric flux less than 1000C, a slump of 200-220mm, and a slump loss of less than 30mm over 4h. At the same time, the concrete components produced have good visual quality, and the surface of the concrete components visible within a range of 5 meters is smooth and flat, without cracks, obvious pores and color difference. It can be used in concrete buildings and structures in ultra-high altitude areas, especially in plain concrete structures, and has broad application prospects. DETAILED DESCRIPTION

[0022] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0023] The invention discloses a large-volume and high-fluidity anti-cracking concrete for ultra-high altitude areas, comprising cement, a foam stabilizer and humidity regulator, an anti-cracking toughening agent, fly ash, mineral powder, fine aggregate, coarse aggregate, a slow-setting high-efficiency water reducing agent, an air entraining agent and water. The concrete comprises 8% to 16% of cement, 0.0001% to 0.001% of a foam stabilizer and humidity regulator, 0.1% to 1.0% of an anti-cracking toughening agent, 3% to 6% of fly ash, 0% to 4% of mineral powder, 28% to 35% of fine aggregate, 42% to 45% of coarse aggregate, 0.001% to 0.002% of a slow-setting high-efficiency water reducing agent, 0.001% to 0.002% of an air entraining agent and 5.5% to 6.5% of water in a weight ratio, wherein:

[0024] (1) Raw materials

[0025] The cement is medium-heat silicate cement, with a strength grade of not less than 42.5 and a specific surface area of ​​300 to 350 m 2 / kg, by adding medium-heat silicate cement, the hydration temperature rise of concrete can be reduced.

[0026] The foam stabilizing and humidity regulating agent is a combination of any two or more of polyvinyl alcohol, calcium stearate, methyl cellulose, carboxymethyl cellulose, carboxymethyl hydroxyethyl cellulose, hydroxypropyl cellulose or polyacrylate. The foam stabilizing and humidity regulating agent is reasonably configured according to the different raw materials, so that the viscosity of the configured foam stabilizing and humidity regulating agent is 20×10 5 ~200×10 5 Pa·S, water absorption rate is 10% to 20%. During the hydration process of concrete, the foam stabilizer and humidity regulator can continuously replenish the moisture of the concrete, maintain the relative humidity inside the concrete, slow down the moisture loss caused by evaporation inside the concrete, reduce concrete shrinkage, improve the mid- and late-stage strength of the concrete, improve the frost resistance of the concrete and the sensory quality of the components, and reduce the risk of early cracking of the concrete.

[0027] The anti-cracking toughening agent is a composition of silica powder and metakaolin, wherein the silica powder content is 50% to 90%, and the metakaolin content is 10% to 50%. The silica powder and metakaolin are reasonably configured so that the content of SiO2 in the configured anti-cracking toughening agent is not less than 90%, and the content of Al2O3 is not less than 5%. The particle size of the anti-cracking toughening agent is 50 to 200 nm. The anti-cracking toughening agent can be filled between particles of cement, mineral powder, fly ash, etc., refine the pores of concrete, greatly improve the strength and density of concrete, reduce the evaporation of water inside and on the surface of concrete, reduce the brittleness of concrete, thereby reducing the risk of early cracking of concrete, and at the same time can greatly improve the chemical erosion resistance, frost resistance and impermeability of concrete.

[0028] By adding foam stabilizers and humidity regulators and anti-cracking toughening agents, the viscosity of the concrete slurry is increased, and the strength and elasticity of the bubble membrane inside the concrete are enhanced, thereby forming a stable liquid film, avoiding the aggregation of bubbles to form large voids, and contributing to the stability of the bubble slurry and the formation of uniform porous materials, effectively increasing the air content of concrete, improving the stability and fluidity of concrete mixtures, improving the homogeneity of concrete, reducing internal defects in concrete, and reducing the risk of cracking.

[0029] The fly ash is Class F II fly ash that meets the standard of GB / T1596-2017 "Fly ash used in cement and concrete", and its water demand ratio is 90% to 100%. By adding fly ash, the amount of water reducer is reduced, the fluidity of concrete is improved, the hydration heat and shrinkage, early elastic modulus and brittleness of concrete are reduced, the density of concrete is improved, the later strength of concrete is improved, the pore structure and workability of concrete are improved, the microcracks inside concrete are reduced, the density of concrete is improved, and the chemical corrosion resistance, frost resistance and impermeability of concrete are improved.

[0030] The mineral powder is granulated blast furnace slag powder of grade S75 or above that meets the standard of GB / T18046-2017 "Granulated blast furnace slag powder for cement, mortar and concrete", and its activity index is not less than 75%, and its specific surface area is not more than 450m 2 / kg, the loss on ignition is not more than 2.5%. By adding mineral powder, the dosage of water reducer is reduced, which can reduce the hydration heat, shrinkage and brittleness of concrete, increase the viscosity of concrete mixture, improve the workability of concrete, increase the density of concrete, and at the same time improve the early strength of concrete, improve the pore structure of concrete, reduce the micro cracks inside concrete, increase the density of concrete, and improve the concrete's resistance to chemical erosion, frost resistance and impermeability.

[0031] The fine aggregate is one of machine-made sand, river sand or mixed sand that complies with GB / T 14684-2022 "Sand for Construction", and the fineness modulus of the fine aggregate is 2.5-2.9; when the sand is machine-made sand, the stone powder content in the machine-made sand is 5%-10%; when the sand is river sand, the mud content of the river sand is not more than 2.0%; when the sand is mixed sand, the mud block content in the mixed sand is not more than 1.0%; the coarse aggregate is a continuously graded crushed stone with a particle size of 5-30 mm that complies with GB / T 14685-2022 "Pebble and Crushed Stone for Construction", and the type of crushed stone is one of limestone, basalt, andesite, gneiss, and quartzite, among which 5-10 mm graded crushed stone, 10-20 mm graded crushed stone and 20-30 mm graded crushed stone need to be mixed in proportion so that the compact porosity of the mixed crushed stone is not more than 40%. By properly grading coarse and fine aggregates, the void ratio of tightly packed aggregates can be reduced, thereby reducing the water consumption of concrete and the amount of adhesive, thereby reducing the shrinkage of concrete, reducing the risk of early cracking of concrete, and making the fluidity of concrete meet construction requirements.

[0032] The retarding high-efficiency water-reducing agent is a combination of any two or more of polycarboxylates, aminosulfonates, naphthalenesulfonic acid formaldehyde condensates, hydroxycarboxylates or phosphates. The retarding high-efficiency water-reducing agent is reasonably configured according to different raw materials, so that the water reduction rate of the configured retarding high-efficiency water-reducing agent is not less than 30%, the initial setting time is not less than 110 minutes, and the setting time difference is 100 minutes to 120 minutes. By adding the retarding water-reducing agent, the adsorption amount of the water-reducing agent on the surface of cement particles is increased, the fluidity of concrete is improved, the temperature rise rate of concrete is delayed, and the time loss of the fluidity of the concrete mixture is reduced.

[0033] The air entraining agent is a combination of any two or more of rosin soaps, tripterygium saponins or polyether polyols. The air entraining agent is reasonably configured according to different raw materials, so that the water reduction rate of the configured air entraining agent is not less than 8%, and the air content is not less than 4%. By adding the air entraining agent, the microstructure of the concrete is improved, the bubble spacing coefficient of the concrete is greatly reduced, and the frost resistance of the concrete in low temperature and large temperature difference environments in ultra-high altitude areas is guaranteed.

[0034] (2) Preparation method

[0035] The following steps are involved:

[0036] S01. Use a forced mixer to add cement, fly ash, mineral powder and anti-cracking toughening agent in proportion and stir for 30 seconds. The stirring speed of the forced mixer is 60-100r / min;

[0037] S02, continue to add water to the forced mixer and stir for 30 seconds, then add air entraining agent, slow setting high-efficiency water reducing agent and foam stabilizing and humidity regulating agent and continue stirring for 30 seconds;

[0038] S03, continue to add sand and gravel into the forced mixer and mix for 30 seconds;

[0039] S04. Discharge the evenly mixed concrete from the mixer.

[0040] Among them, the time from unloading concrete from the mixer to starting pouring shall not exceed 2 hours.

[0041] The cement used in the following examples and comparative examples is Esheng P.MH42.5 medium-heat silicate cement with a specific surface area of ​​336 m 2 / kg; the fly ash used is Class F II fly ash from Huadian Ningxia Lingwu Power Generation Co., Ltd., with a water requirement ratio of 100%; the mineral powder used is S95 grade mineral powder from Chengdu Jinzhu New Materials Co., Ltd., with an activity index of 98% and a specific surface area of ​​432m 2 / kg, with a loss on ignition of 0.25%; the sand used is the machine-made sand from the self-mined machine-made sand and gravel aggregate field in Jiaba Township, Kangding, with a sand fineness modulus of 2.7 and a stone powder content of 7%; the crushed stone used is limestone from the self-mined machine-made sand and gravel aggregate field in Jiaba Township, Kangding, which is a mixture of 5-10mm crushed stone, 10-20mm crushed stone, and 20-30mm crushed stone in a ratio of 2:5:3, and the compact porosity of the mixed crushed stone is 37%; the foam stabilizer and humidity regulator used is calcium stearate and polyacrylic acid in a weight ratio of 7:3, and its viscosity is 20×10 5 ~200×10 5 Pa·S, water absorption rate is 20%; the anti-cracking toughening agent used is silica powder and metakaolin in a weight ratio of 9:1, wherein the content of SiO2 is 92%, the content of Al2O3 is not less than 7%, and the particle size of the anti-cracking toughening agent is 50-200nm; the slow-setting high-efficiency water-reducing agent used is polycarboxylate and sodium phosphate in a weight ratio of 10:1, wherein the polycarboxylate is produced by Shanxi Jinkaiqi Building Materials Technology Co., Ltd., and the sodium phosphate is produced by Shifang Chemical Plant in Sichuan Province, and its water reduction rate is 32%, the initial setting time is 615min, and the setting time difference is 110min; the air-entraining agent used is triterpenoid saponin and polypropylene glycol in a weight ratio of 4:6, and its water reduction rate is 9%, and the air content is 4.5%.

[0042] Table 1 lists the components and weight ratios of Examples 1 to 5 and Comparative Examples 1 to 3.

[0043]

[0044] The concrete design strength grade of Example 1, Example 2 and Comparative Example 1 is C35, the concrete design strength grade of Example 3, Example 4 and Comparative Example 2 is C45, and the concrete design strength grade of Example 5 and Comparative Example 3 is C50.

[0045] The preparation method of the large-volume, high-fluidity, crack-resistant concrete of the above embodiments and comparative examples is as follows:

[0046] S01. Add cement, fly ash, mineral powder and anti-cracking toughening agent into the forced mixer in proportion and stir for 30 seconds. The stirring speed of the forced mixer is 80r / min.

[0047] S02, continue to add water into the forced mixer and stir for 30 seconds, then add air entraining agent, slow setting high-efficiency water reducing agent and foam stabilizing and humidity regulating agent in proportion and continue stirring for 30 seconds;

[0048] S03, continue to add sand and gravel into the forced mixer and mix for 30 seconds;

[0049] S04. Discharge the uniformly mixed concrete from the mixer to obtain a concrete mixture.

[0050] The concrete mixture prepared in the ultra-high altitude environment was tested for slump and 4h slump loss at room temperature in the ultra-high altitude environment according to GB / T50080-2016 "Standard for Test Methods for Performance of Ordinary Concrete Mixtures"; the concrete was molded into test blocks and cured to the age, and the 56-day compressive strength and 3-day strength tension-compression ratio (cracking resistance index) of the concrete blocks at room temperature in the ultra-high altitude environment were tested according to GB / T50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete"; the frost resistance grade, impermeability grade and electrical flux of the concrete blocks at room temperature in the ultra-high altitude environment were tested according to GB / T50082-2009 "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete". The specific test results are shown in Table 2.

[0051] Table 2 lists the performance test results of Examples 1 to 5 and Comparative Examples 1 to 3.

[0052]

[0053]

[0054] It can be seen from Tables 1 and 2 that the performance of the large-volume, high-fluidity, crack-resistant concrete prepared by the raw materials and methods of Examples 1 to 5 in ultra-high altitude areas is better than that of the ordinary large-volume, high-fluidity, crack-resistant concrete, the 3-day strength tension-compression ratio of the concrete is greater than 8%, the 56-day compressive strength is 40-75Mpa, the frost resistance grade is greater than F450, the impermeability grade is not less than P14, the electric flux is less than 1000C, the slump is 200-220mm, and the slump loss over time of 4h is less than 30mm. At the same time, the visual quality of the prepared concrete components is good, and the surface of the concrete components visible within a range of 5 meters is smooth and flat, without cracks, obvious pores and color difference.

[0055] The present invention achieves the synergistic effect among the components by adjusting the proportion of the components of concrete or changing the proportion of the main components of concrete, thereby improving the stability of large-volume and high-fluidity concrete mixtures and reducing the hydration temperature rise and shrinkage of concrete; the process of the present invention is used to prepare concrete, so that the components of the concrete are evenly distributed in the structure, thereby reducing the internal defects and brittleness of the concrete, increasing the density and strength of the concrete, and greatly reducing the risk of concrete cracking. At the same time, the frost resistance, impermeability, chemical corrosion resistance and apparent quality of the concrete are greatly improved, and the durability of the concrete is effectively improved.

[0056] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A large-volume, high-fluidity, crack-resistant concrete for ultra-high altitude areas. Features: The invention comprises cement, foam stabilizer and humidity regulator, anti-cracking and toughening agent, fly ash, mineral powder, fine aggregate, coarse aggregate, slow-setting and high-efficiency water reducing agent, air entraining agent and water, wherein the weight ratio is 8% to 16% of cement, 0.0001% to 0.001% of foam stabilizer and humidity regulator, 0.1% to 1.0% of anti-cracking and toughening agent, 3% to 6% of fly ash, 0% to 4% of mineral powder, 28% to 35% of fine aggregate, 42% to 45% of coarse aggregate, 0.001% to 0.002% of slow-setting and high-efficiency water reducing agent, 0.001% to 0.002% of air entraining agent and 5.5% to 6.5% of water. The cement is medium-heat silicate cement, and its strength grade is not less than 42.5, and its specific surface area is 300 to 350 m 2 / kg, the foam stabilizing and humidity regulating agent is a combination of any two or more of polyvinyl alcohol, calcium stearate, methyl cellulose, carboxymethyl cellulose, carboxymethyl hydroxyethyl cellulose, hydroxypropyl cellulose or polyacrylate, and the viscosity of the foam stabilizing and humidity regulating agent is 20×10 5 ~200×10 5 Pa∙S, the water absorption rate is 10% to 20%, the anti-cracking toughening agent is a composition of silica powder and metakaolin, and the SiO 2 The content of not less than 90%, Al 2 O 3 The content of is not less than 5%, the particle size of the anti-cracking toughening agent is 50-200nm, the retarding high-efficiency water-reducing agent is a combination of any two or more of polycarboxylates, aminosulfonates, naphthalenesulfonic acid formaldehyde condensates, hydroxycarboxylates or phosphates, the water reduction rate of the retarding high-efficiency water-reducing agent is not less than 30%, the initial setting time is not less than 110min, and the setting time difference is 80min-120min.

2. The large-volume, high-fluidity, crack-resistant concrete for ultra-high altitude areas according to claim 1, Features: The fly ash is Class F II fly ash, and its water requirement ratio is 90% to 100%; the slag powder is granulated blast furnace slag powder of S75 or above, and its activity index is not less than 75%, and its specific surface area is not more than 450m 2 / kg, loss on ignition is not more than 2.5%.

3. The large-volume, high-fluidity, crack-resistant concrete for ultra-high altitude areas according to claim 1, Features: The fine aggregate is one of machine-made sand, river sand or mixed sand, and its fineness modulus is 2.5-2.9; when the fine aggregate is machine-made sand, the stone powder content in the machine-made sand is 5%-10%; when the fine aggregate is river sand, the mud content of the river sand is not more than 2.0%; when the fine aggregate is mixed sand, the mud block content in the mixed sand is not more than 1%; the coarse aggregate is continuously graded crushed stone with a particle size of 5-30 mm, and the type of crushed stone is one of limestone, basalt, andesite, gneiss or quartzite, among which 5-10 mm graded crushed stone, 10-20 mm graded crushed stone and 20-30 mm graded crushed stone need to be mixed in proportion, and the compact porosity of the mixed crushed stone is not more than 40%.

4. The large-volume, high-fluidity, crack-resistant concrete for ultra-high altitude areas according to claim 1, Features: The air entraining agent is a combination of any two or more of rosin soaps, tripterygium saponins or polyether polyols, and the water reduction rate of the air entraining agent is not less than 8%, and the air content is not less than 4%.

5. A method for preparing a large-volume, high-fluidity, crack-resistant concrete for ultra-high altitude areas according to any one of claims 1 to 4, Features The following steps are involved: S01. Use a forced mixer to add cement, fly ash, mineral powder and anti-cracking toughening agent in proportion and stir for 30 seconds, wherein the stirring speed of the forced mixer is 60r / min~100r / min; S02, continue to add water to the forced mixer and stir for 30 seconds, then add air entraining agent, slow setting high-efficiency water reducing agent and foam stabilizing and humidity regulating agent and continue stirring for 30 seconds; S03, continue to add sand and gravel into the forced mixer and mix for 30 seconds; S04. Discharge the evenly mixed concrete from the mixer.